Work-Family Climate and Work-Family Conflict on Medical Representative - Rusmalia Dewi; Joniarto Parung; Artiawati Artiawati (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2021)
Work climate organization is one of the reasons why work-family conflict occurs. Although research on work-family climate and work-family conflict has been widely carried out in Europe and America, there are still few studies that examine the relationship between the two in Asia, especially in Indonesia. This study aims to examine the relationship between work-family climate and work-family conflict at medical representatives. The method used is quantitative by collecting data through purposive sampling technique and using 105 medical representative respondents who are married and have children. Using Kossek's work-family climate scale and Carlson's standard work-family conflict scale adapted by Artiawati. Data were analyzed using regression analysis. The results of the study simultaneously obtained F = 5.487 p <0.021, which means that there is a relationship between work-family climate and family work conflicts at medical representatives in Indonesia. This result further strengthens that the work-family climate has a relationship with work-family conflict in medical representatives in Indonesia, but partially the work climate has no correlation with work-family conflict. This study concludes that if work-family claims share concerns and make sacrifices well, it can reduce work-family conflict for medical representatives.